Synergistic effects of sugar beet pectin and laccase on gel properties of egg white - Minquan Xia; Haobo Jin; Wanyi Dong; Zhaoxia Cai (Food Science of Animal Products, 2023)
It is of great significance to improve the gel properties of egg white for their related products. This goal was accomplished by investigating the gel properties of egg white via interacting with pectin and laccase, and revealing their mechanisms. Results showed that 0.06% sugar beet pectin (SBP) and 0.5 U/g laccase could endow egg white gels with better texture properties (with the highest hardness of 1 508.00 g, chewiness of 1 144.83, and gumminess of 1 210.57), and superior water holding capacity (WHC) (the highest WHC value of 72.08%). This was attributed to the fact that 0.06% of SBP filled the pores of egg white gel, and enhanced affinity and binding of the gels to water by the good hydrophilicity of SBP, and the decrease in egg white gel pore size. Laccase (0.5 U/g) could promote the cross-linking between the egg white gel and SBP to form a more complex gel network structure through the interactions between the tyrosine residues and ferulic acid in SBP, which brought more ionic bonds (22.47%), hydrogen bonds (12.4%), disulfide bonds (16.97%) and more compact structure to egg white gels. This work can provide an effective method to improve the quality of egg white gel and related products.